The constitutional review of the clarity of referenda questions - Miloš, Matija (Array, 2020)
The paper explores the requirement of clarity of referenda questions. More specifically, it revisits the critique levelled against its enforcement by (constitutional) courts. Some scholars argue that clarity cannot be specified through apolitical reasoning and that politically unaccountable judges do not have the legitimacy to narrow down its meaning. While the paper does not dispute the indeterminacy of clarity, it does suggest an alternative to the complete rejection of judicial review. Such a rejection assumes that all cases of judicial oversight of clarity are of the same type. A more nuanced perspective, developed in the paper, strives to find ways to differentiate cases where judicial oversight was conducted in a manner that facilitates democratic processes from those where the legal argument is deployed as an obstruction. This is impossible to do outside each individual case. Having this in mind, the paper shows how judicial review of clarity may be understood as a project of describing different democratic processes that may co-exist in a constitutional democracy. This allows the courts to apply clarity in a context-specific manner and enables a more nuanced political response. The framework developed in the paper can be used to investigate individual disputes over the clarity of referendum questions.